Single Nucleotide Polymorphisms (SNPs) in Exon 6 of Lecithin Cholesterol Acyltransferase (LCAT) Gene in Indonesian Local Sheep - . Hidayati; Cece Sumantri; RR Noor; R Priyanto (Faculty of Animal Science, Bogor Agricultural University, 2014)
Lecithin cholesterol acyltransferase (LCAT) is a soluble enzyme that converts cholesterol and lecithin to cholesteryl esters and lysolecithins on the surface of high density lipoprotein and plays an important role in lipoprotein metabolism. The research was aimed to explore single nucleotide polymorphisms of LCAT gene in Indonesian local sheep. A total of 118 genomic DNA of Indonesian local sheep were used in this research, consisted of Sumatera Thin Tail (43 heads), Garut (19 heads), Javanese Thin Tail (17 heads), Javanese Fat Tail (6 heads), Rote Island (7 heads), Kissar (7 heads), Sumbawa (10 heads), and Lembah Palu (9 heads). Polymerase chain reaction was used to amplify genomic DNA for exon 6 (250 bp) and direct sequencing method was used to identify polymorphism sequences. The sequences were analyzed with BioEdit and MEGA 5.2 software. The BLAST sequence was obtained from Gene Bank GQ 150556.1. The results showed three novel SNPs, i.e. c.742C>T, c.770 T>A and c.882C>T. Substitution of cytosine to thymine c.742 is a synonymous mutation; thymine to adenine c.770 and cytosine to thymine c.882 are non-synonymous mutations. Polymorphisms of LCAT gene exon 6 was found in Sumatera Thin Tail, Javanese Thin Tail, Javanese Fat Tail, Garut, Lembah Palu, and Rote Island.